Strength and functional conditioning training: analyzing practitioners' perceptions - Rafael David; António Manuel Azevedo; Paulo Eira (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Currently, both recreational participants and athletes are required to maintain fitness levels that enable them to endure the specific physical demands of their activities for longer periods. At the same time, they must be able to perform high-level technical movements during various sports activities, which are carefully planned to improve physical condition, well-being, and quality of life.